Mania associated olfactory dysfunction: A comparison between bipolar subjects in mania and remission. (December 2022) - Kazour, Francois; Atanasova, Boriana; Mourad, Marc; El Hachem, Charline; Desmidt, Thomas; Richa, Sami; El-Hage, Wissam
Abstract: Objectives: The aim of this study was to assess the olfactory functions of patients with bipolar disorder in manic phase and to compare them to those of bipolar subjects in remission and healthy controls. Methods: We recruited 96 participants divided in 3 groups: bipolar mania (MB), euthymic bipolar in remission (EB) and healthy controls (HC). All participants underwent an assessment of their olfactory functions using the Sniffin' sticks threshold and identification tests. Odors' pleasantness, intensity, familiarity and emotion were assessed. All participants were screened for the presence of psychiatric disorder through the MINI questionnaire. Clinical evaluation explored dimensions of mania, depression, anxiety respectively through YMRS, MADRS and STAI scales. Anhedonia was explored through the Chapman physical and social anhedonia questionnaire. Results: Patients in mania had deficits in identifying positive smells compared to bipolar subjects in remission and to healthy controls (MB < EB < HC; p < 0.001). Hedonic (MB < EB = HC; p < 0.001) and emotional (MB < EB = HC; p < 0.001) ratings of positive smells were lower in patients in manic phase compared to remitted subjects or controls. Mania was associated to higher emotion rating of negative smells compared to remitted subjects and controls (MB > EB = HC; p < 0.001). There was no difference between the 3 groups in the ratings of intensity and familiarity of smells, as well as in the olfactory threshold testing. The 3 groups showed no difference in the identification of negative smells. Conclusions: Patients in manic episodes showed deficits in identifying positive odors. They evaluated these smells as less pleasant and less emotional compared to remitted bipolar subjects and healthy controls. These olfactory dysfunctions may constitute potential indicators of manic state. The persistence of olfactory dysfunction in remission phase (deficit in the olfactory identification of positive odors compared to healthy controls) may constitute a potential trait indicator of bipolarity.